Weight loss and wrestling training: effects on growth-related hormones - Roemmich, J. N.; Sinning, W. E. (Journal of Applied Physiology, 1997)
Adolescent wrestlers (n = 9, 15.4 yr) and recreationally active control males (n = 7, 15.7 yr) were measured before, at the end of, and 3.5-4 mo after a competitive wrestling season to assess the influence of dietary restriction on growth-related hormones. Wrestlers had significant elevations preseason to late season for morning serum concentrations (mean of 8 serial samples) of growth hormone (GH; 2.9 +/- 0.7 vs. 6.5 +/- 1.4 ng/ml) and sex hormone-binding globulin (SHBG; 16.1 +/- 2.3 vs. 27.9 +/- 6.9 nmol/l) and significant reductions in GH-binding protein (GHBP; 178 +/- 19 vs. 109 +/- 17 pmol/l), insulin-like growth factor I (IGF-I; 332 +/- 30 vs. 267 +/- 34 ng/ml), testosterone (T; 4.9 +/- 0.4 vs. 3.6 +/- 0.4 ng/ml), and free testosterone (Free-T; 22.4 +/- 3.6 vs. 15.7 +/- 2.8 pg/ml). Wrestlers had significant postseason reductions in GH (3.44 +/- 1.30 ng/ml) and SHBG (10.43 +/- 4.13 nmol/l) but elevations in GHBP (66.7 +/- 23.8 pmol/l), IGF-I (72.9 +/- 25.1 ng/ml), T (2.10 +/- 0.46 ng/ml), and Free-T (9.76 +/- 3.01 pg/ml). Concentrations of luteinizing hormone (LH), estradiol, prolactin, cortisol, insulin, and thyroid hormones did not differ because of exercise-dietary practices of wrestlers. In-season elevations in GH, with concomitant reductions in GHBP and IGF-I, that were reversed during the postseason suggest a reduction in GH receptor number and partial GH resistance during the season. Nonelevated LH with reduced T levels suggests a central hypothalamic-pituitary-gonadal (H-P-G) axis impairment. In conclusion, undernutrition may lead to altered H-P-G and GH-IGF-I axes function in adolescent wrestlers. However, only the wrestlers' late-season Free-T concentrations were outside the normal range, and the hormone axis impairments were quickly reversed. The present data do not address hormonal axis responses to several years of wrestling and weight loss.